Turnover of compulsory school principals in Iceland from 1998 to 2020 - Hansen, Börkur; Björnsdóttir, Amalía (Menntavísindasvið Háskóla Íslands, 2024)
Turnover of principals is an issue of concern in many countries, including Iceland (Börkur Hansen, 2021). To a large extent, interest in turnover is based on research findings that show the importance of retaining school principals for sustaining good practices and student learning (Béteille et al., 2011; Hargreaves amp; Fink, 2006; Seashore-Louis et al., 2010). However, turnover of school principals is not extensively researched, with the main accessible studies coming from the US and some from Sweden (Rangel, 2018; Thelin, 2020). According to Rangel (2018), the main concepts used in these studies are “stayers”, “movers”, “mobility” and “stability”. Sigurbjörg Róbertsdóttir et al. (2019) state that the role of compulsory school principals in Iceland is rapidly changing, primarily due to the addition of new tasks to their roles and increased pressure for academic achievement. They claim that this development has led to decreased job satisfaction, increased stress, and fewer applications for vacant positions of compulsory school principals. Kaplan amp; Owings (2015) paint a similar picture of the situation in the US, where demands on principals have become unrealistic, resulting in high turnover and fewer people applying for the job. Pritchard (2019) reports that 25% of school principals in the US quit their job every year, and around 50% of new principals quit after three years. Seashore-Louis et al. (2010) argue that poorly planned exchanges of principals can have a negative impact on student learning. They highlight that successful work may be disrupted when new people take over and the replacement has been inadequately planned. The findings of the International Successful School Principalship Project (ISSPP) point in the same direction (Moos et al., 2011). Hargreaves amp; Fink (2006) agree and focus on the importance of ensuring that the leadership of principals does not weaken or disappear when a new person is hired. Lee (2015) further emphasizes that succession planning for principals should not be left to ...